Role of Lone‐Pairs in Driving Ferroelectricity of Perovskite Oxides: An Orbital Selective External Potential Study. Issue 6 (15th April 2019) - Shen, Yang; Cai, Jia; Ding, Hang‐Chen; Shen, Xin‐Wei; Fang, Yue‐Wen; Tong, Wen‐Yi; Wan, Xian‐Gang; Zhao, Qingbiao; Duan, Chun‐Gang
Abstract: The orbital selective external potential (OSEP) method, recently developed by the authors, allows the energy level of a specific atomic orbital to be shifted, thus allowing for the identification of the role of this orbital in the chemical and physical properties of the system. Using OSEP, the origins of ferroelectricity in two classic ferroelectric perovskites, BaTiO3 and PbTiO3, are systematically revisited. The fact that the hybridization between the Ti 3d state and the O 2p state is essential for the formation of ferroelectricity in both BaTiO3 and PbTiO3 is reproduced, which validates this method. Particularly, for PbTiO3, the Pb 6s lone‐pair electron states can also be tuned using the OSEP method, and its influence on the ferroelectricity is unveiled in detail. Surprisingly, it is found that the electric dipoles formed by lone‐pair lobes contribute only slightly to the overall ferroelectric polarization, whereas the concomitant ionic displacements and lattice distortions are prominently favorable for ferroelectricity. Indeed, it is found that the Pb–O hybridization plays an important role in the ferroelectricity of PbTiO3, which makes the polarization of PbTiO3 significantly larger than that of BaTiO3 . This study provides a simple yet straightforward way to demonstrate the mechanisms of ferroelectricity in perovskite oxides, which can be applied to the study of ferroelectric mechanism in other relevant materials. Abstract : The orbital selective external potential method acts as an electric field to modulate orbital hybridization by shifting the energy difference Δ, especially lone‐pair by tuning Pb s‐p hybridization. The electric dipoles formed by lone‐pairs and Pb atoms contribute only slightly to ferroelectricity, while ionic displacements and lattice distortions driven by lone‐pair stereochemical activity are prominently favorable for ferroelectricity in PbTiO3 .